2010
DOI: 10.1002/casp.1072
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiential journey toward voluntary childlessness: An interpretative phenomenological analysis

Abstract: Voluntary childlessness is a relatively novel yet growing phenomenon. It has implications on fertility rates, our ageing society, health and social care, and economic growth. This idiographic study explored three women's experiential journeys toward voluntary childlessness to help understand this phenomenon and its impact on contemporary society. Semi-structured interviews were carried out and analyzed using Interpretative Phenomenological Analysis. Themes identified were: the legacy of feminism, models of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 22 publications
5
35
1
1
Order By: Relevance
“…Childfree women 3 Voluntarily Childfree Women: A Phenomenological Exploration of the Childfree Choice Women who 'reject' the notion of motherhood and choose to remain childfree are a relatively new and growing cohort in industrialised countries (Abma & Martinez, 2006;Park, 2005;Rowland, 2007;Shaw, 2011). A survey of 7,448 Australian women aged from 22 to 27 years revealed that 9.1% desire to remain childfree The conscious choice to remain childless automatically places women outside the constraints of cultural and societal expectations underpinned by an ideology of pronatalism (Park, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childfree women 3 Voluntarily Childfree Women: A Phenomenological Exploration of the Childfree Choice Women who 'reject' the notion of motherhood and choose to remain childfree are a relatively new and growing cohort in industrialised countries (Abma & Martinez, 2006;Park, 2005;Rowland, 2007;Shaw, 2011). A survey of 7,448 Australian women aged from 22 to 27 years revealed that 9.1% desire to remain childfree The conscious choice to remain childless automatically places women outside the constraints of cultural and societal expectations underpinned by an ideology of pronatalism (Park, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ten voluntarily childfree women participated in a qualitative study in which unstructured interviews ensured each woman's unique story emerged through its telling. The data analysis revealed three broad themes -first, the experiences and processes of making the choice; second, the ongoing effects of their choice, ranging from support and acceptance to pressure and discrimination; and finally, there was no regret as the women described engaging in meaningful, generative activities that contributed to society.Childfree women 3 Voluntarily Childfree Women: A Phenomenological Exploration of the Childfree Choice Women who 'reject' the notion of motherhood and choose to remain childfree are a relatively new and growing cohort in industrialised countries (Abma & Martinez, 2006;Park, 2005;Rowland, 2007;Shaw, 2011). A survey of 7,448 Australian women aged from 22 to 27 years revealed that 9.1% desire to remain childfree The conscious choice to remain childless automatically places women outside the constraints of cultural and societal expectations underpinned by an ideology of pronatalism (Park, 2005).…”
mentioning
confidence: 99%
“…IPA studies require a homogenous sample [35,48]. At baseline, the Caucasian sample of seven participants (of whom five were female) ranged in age from 39 -58 years…”
Section: Design and Participantsmentioning
confidence: 99%
“…This is reflected in the negative attitudes held societally towards those who either cannot or do not have children (Gillespie, 2000;Letherby, 1999;Shaw, 2011). As a result of this, in relation to motherhood, the only relevant question is not 'if' women will have children, but 'when', with 'older mothers' being those that are simply 'delaying the inevitable' (Smajdor, 2009).…”
Section: Timing Motherhood and The Biological Clockmentioning
confidence: 99%